ASSESSMENT OF GROWTH CHARACTERISTICS AND THE SURVIVAL RATE OF PACIFIC WHITE SHRIMP LITOPENAEUS VANNAMEI (BOONE, 1931), REARED WITH DIFFERENT STOCKING DENSITIES IN THE COASTAL PONDS, SINDH, PAKISTAN - Habib Ul Hassan; M. A. Siddique; M. F. A. Abdel-Aziz; K. Gabol; A. E. Ahmed; M.S. Parvez (Journal of Animal and Plant Sciences, 2022)
Stocking density is one of the crucial factors affecting the growth and survival of Pacific white shrimp. A suitable density is critical in culture shrimp, balancing the production as quantity and marketing as quality. Therefore, the present study optimized stocking density for pacific white shrimp reared in the pond ecosystem in Pakistan. The initial weight of postlarvae was (0.003±0.001 grams), were stocked in 3 stocking densities (Treatment1- 133.3 PL/m2, Treatment 2- 300 PL/m2, and Treatment 3- 466.6PL/m2) for 114 days. The water quality parameters were ranged between (29.3-30.2° C), (5.1-5.5 mg/L), (5.8-7.3), (24.16-24.44 ppt.), (118-120 mg/L), (0.29-0.41 mg/L), (0.97-1.51mg/L), (0.08-0.09 mg/L), (0.02-0.12 mg/L) and (560.66-610 mg/L) for temperature, DO, pH, salinity, alkalinity, phosphate, nitrate, nitrite, ammonium nitrogen and TSS, respectively. Treatment 1 had the highest final weight (24.30±0.90 g), final length (15.8±0.30 cm), average daily gain (0.21g /day), weight gain (24.29 g) and Viscerosomatic index (4.6 g), which was significantly different compared to treatment 2 and treatment 3 (p<0.05). SGR did not differ significantly (p>0.05) between treatment 1 (7.64 % /day) and treatment 2 (7.63% /day) but significantly higher than the treatment 3 (7.10 %/ day). The Hepatosomatic index and Fulton’s condition factor were not significantly varied among the treatments. Treatment 1 had the best FCR (1.11) compared to the other treatments. The survival rate of shrimp significantly varied among these treatments (p<0.05) and treatment 1 had the highest survival rate (90.6%), followed by treatment 2 (82.20%) and treatment 3 (75.38%). Moreover, polynomial regression showed that from 133.3 PL/m2 to 240 PL/m2 is an excellent stocking density for L. vannamei. Furthermore, the stoking density from 240 PL/m2 to 460 PL/m2 decreased the growth and survival rate. The present study concluded that the stocking density of L. vannamei at 250-300 PL/m2) can achieve the best growth and survival rate.
Keywords: Litopenaeus vannamei; Stocking density; Growth performance; survival